2020
DOI: 10.13171/mjc104020041156mh
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical study, polyphenols determination and evaluation of antioxidant activity of Origanum compactum and Satureja calamintha nepeta from the region of Ouazzane (Morocco)

Abstract: <p>Among natural remedies, aromatic and medicinal plants constitute an essential source that deserves scientific attention. Thus, our study aims to promote the virtues of two aromatic and medicinal plants found in the wild in the region of Ouazzane (Morocco). The phytochemical tests of these species have shown the presence of flavonoids, gallic and catechic tannins, cyanidin, sterols and triterpenes. However, alkaloids, carotenoids, saponosides and reducing compounds were not detected. Then, extraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A previous phytochemical study of Satureja calamintha extracts collected from the Ouzzane region in Morocco has shown the presence of flavonoids, gallic and catechic tannins, cyanidin, sterols and triterpenes (Hayani et al, 2020). In another study, the three most abundant compounds identified in the essential oils of this species were l-menthone, neo-menthol and pulegone.…”
Section: Phytochemical Screening Of Satureja Calamintha Extractsmentioning
confidence: 76%
“…A previous phytochemical study of Satureja calamintha extracts collected from the Ouzzane region in Morocco has shown the presence of flavonoids, gallic and catechic tannins, cyanidin, sterols and triterpenes (Hayani et al, 2020). In another study, the three most abundant compounds identified in the essential oils of this species were l-menthone, neo-menthol and pulegone.…”
Section: Phytochemical Screening Of Satureja Calamintha Extractsmentioning
confidence: 76%